Use of chinese and western over-the-counter medications in Hong Kong - Yeoh Eng; Yi Wong Eliza; Sze You Joyce; Kin Chan Frank; Lau Chun; Chi Ho Chung Vincent; Griffiths Sian (BMC, 2010)
Abstract Benefits of engaging community pharmacists in providing wider primary care are internationally acknowledged; in Hong Kong, however, strategies for harnessing their potential contributions are yet to be launched. Here, community pharmacist and Chinese medicine retailers are responsible for providing western and Chinese over-the-counter (OTC) medications. Patterns of OTC uses reflect the characteristics of populations who rely on community pharmacists and Chinese medicine retailers as their main point of contact with the healthcare system. Analyzing the data from a Hong Kong survey (n = 33,263) on self medication and medical consultation patterns, we propose, in this article, an extended role for community pharmacists and Chinese medicine retailers, which entails aspects as follows: (1) referring patients to other medical services where appropriate; (2) providing health education and preventative services; (3) safeguarding the use of Chinese herbal medicines.